2021
DOI: 10.1016/j.ctro.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Combining radiotherapy and focused ultrasound for pain palliation of cancer induced bone pain; a stage I/IIa study according to the IDEAL framework

Abstract: Background: Cancer induced bone pain (CIBP) strongly interferes with patient's quality of life. Currently, the standard of care includes external beam radiotherapy (EBRT), resulting in pain relief in approximately 60% of patients. Magnetic Resonance guided High Intensity Focused Ultrasound (MR-HIFU) is a promising treatment modality for CIBP. Methods: A single arm, R-IDEAL stage I/IIa study was conducted. Patients presenting at the department of radiation oncology with symptomatic bone metastases in the append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In the (or "a" or "our") previous research, it was shown that the combined treatment of EBRT and MR-HIFU is feasible and safe. 25 Clinical outcomes were promising and need to be further assessed in this comparative trial.…”
Section: Combined Treatmentmentioning
confidence: 92%
See 2 more Smart Citations
“…In the (or "a" or "our") previous research, it was shown that the combined treatment of EBRT and MR-HIFU is feasible and safe. 25 Clinical outcomes were promising and need to be further assessed in this comparative trial.…”
Section: Combined Treatmentmentioning
confidence: 92%
“…[14][15][16][17][18][19][20][21] Moreover, combining MR-HIFU with EBRT may have a complementary or even synergistic effect on pain response. [22][23][24][25] In an earlier study the feasibility of combined treatment was proven. 25 Still, high quality evidence and context is needed to determine the role of MR-HIFU in the rst-line treatment options of patients with CIBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment included both an "idea" stage (R-IDEAL Stage 1; that is, first-in-human implementation) and a "development" stage (R-IDEAL Stage 2a; that is, reporting technical feasibility "when additional modifications are made to further optimize workflow and technology for innovative treatment delivery." 10 The R-IDEAL conceptual schema allows technology development to be substantiated iteratively as parts of a coherent programmatic project 8,[11][12][13][14][15] and is analogous to the parent IDEAL method for surgery. 16 The aim of the current study was to demonstrate the first-in-human implementation of adaptive MR-guided radiotherapy (MRgRT) for gynecologic external-beam application (R-IDEAL Stage 1).…”
Section: R-ideal Approachmentioning
confidence: 99%
“…However, the integration of these immersible arrays into clinical systems is limited for a couple of reasons. First, these arrays often require a large number of sophisticated transducers that are high-end commercial products such as systems developed by Verasonics Inc. [43], Imasonic SAS [297] and Phillips B.V. [299]. Further, the overall cost in such a system integration is also burdened by the expensive peripheral equipment employed for functions such as pressure amplification and data acquisition.…”
Section: Introductionmentioning
confidence: 99%